Analisis Usability Menggunakan Model USE Questionnaire pada Aplikasi Presensi Magang - Fauzia, Syifa; Yulius, Rina (POLITEKNIK NEGERI JAKARTA, 2024)
This research aims to overcome the problems associated with the attendance system used by PT X. Currently, the attendance system uses RFID technology which has several problems, such as USB cables that are often loose, problems with internet connections, and the vulnerability of the system to fraud. Therefore, it is necessary to update the existing attendance system. The proposed solution is the development of an Android-based attendance application that uses Quick Response Code (QR Code) technology and geolocation. QR Code is a 2-dimensional bar code that has a larger data storage capacity compared to barcodes. Geolocation is used to limit the area of use of the attendance feature which can only submit attendance if the user is in the PT X area. This research consists of 2 stages, namely the application development stage and the application implementation analysis stage. The application development stage uses the System Development Life Cycle (SDLC) method by implementing a prototype model. In the analysis stage, this research uses descriptive quantitative research methods. The analysis was conducted using the USE Questionnaire model. The results of the usability analysis of the internship attendance application get a score of 87.74% so that based on the USE rating the application is categorized as very feasible.